Magnetoelectric Studies on Curcumin : Analysis of Voltage and Conductivity in Electrochemical Mediums Based Fuzzy Logic - Zainal Abidin; Rifqi Aishatul Faroh; Eko Wahyu Santoso (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
In the curcumin compound there are aromatic compounds that have electronic spins on each side of the benzene. In previous research, the concentration of curcumin and H2O as coatings on copper coils could provide physical changes to the characteristics of copper coils, namely increasing the strength of the magnetic field and increasing the electric current in the coil. The fuzzification process can be described using membership variables with concentrations of curcumin and H2O as input, magnetic field strength and current as output. It is known that the greatest concentration of curcumin indicates increased magnetic field strength and electric current. Simulation of the aromatic spin on the curcumin compound as an Op Amp shows that the highest curcumin concentration value results in an increase in the output voltage (Vout).